2009
DOI: 10.1038/emboj.2009.206
|View full text |Cite
|
Sign up to set email alerts
|

PARP is activated at stalled forks to mediate Mre11-dependent replication restart and recombination

Abstract: If replication forks are perturbed, a multifaceted response including several DNA repair and cell cycle checkpoint pathways is activated to ensure faithful DNA replication. Here, we show that poly(ADP-ribose) polymerase 1 (PARP1) binds to and is activated by stalled replication forks that contain small gaps. PARP1 collaborates with Mre11 to promote replication fork restart after release from replication blocks, most likely by recruiting Mre11 to the replication fork to promote resection of DNA. Both PARP1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
528
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 539 publications
(559 citation statements)
references
References 65 publications
20
528
2
1
Order By: Relevance
“…Of note, the binding of p-RPA to the replication fork was also induced after HU, but it was less in PARP1 À / À cells (Fig. 2e), possibly because of PARP1's role in MRN-mediated resection at the replication fork that activates ATR 48 . Despite a great effort, all available PAR and PARP1 antibodies failed to visualize PAR and PARP1 binding at the replication fork, probably because of stringent technical requirement of this assay.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Of note, the binding of p-RPA to the replication fork was also induced after HU, but it was less in PARP1 À / À cells (Fig. 2e), possibly because of PARP1's role in MRN-mediated resection at the replication fork that activates ATR 48 . Despite a great effort, all available PAR and PARP1 antibodies failed to visualize PAR and PARP1 binding at the replication fork, probably because of stringent technical requirement of this assay.…”
Section: Resultsmentioning
confidence: 98%
“…S2). As PARP1 is required for the recruitment of the MRN complex to resect DNA at the stalled replication forks 58,59 , the impaired activation of Chk1 in PAR-deficient conditions might be due to the decreased resection at stalled forks, leading to less RPA-ATR-Chk1 activation. However, since ATR is dispensable for Chk1-PAR binding and Chk1 is enriched at the replication fork without HU treatment, less p-RPA after damage is unlikely to contribute significantly to the accelerated dissociation of Chk1 from the replication fork.…”
Section: Discussionmentioning
confidence: 99%
“…PARP-1 has been described to participate in double strand break repair [37]. Nicolás and co-workers have identified the accumulation of double strand breaks in PARP-2 -/-murine thymocytes [38].…”
Section: Parp-2 In the Maintenance Of Genomic Integritymentioning
confidence: 99%
“…This observation is in line with previous report by Yelamos and colleagues [24] who suggested that PARP-2 interacts with the Ku proteins, mediators of double strand break repair. Moreover, Robert and colleagues have identified PARP-2 as a suppressor of recombination during immunoglobulin class switch events in murine and human B cells [39], while Bryant et al have suggested that both PARP-1 and -2 are essential in resolving blocked replication forks by homologous recombination in CHO and murine embryonic fibroblasts (MEFs) [37,40]. The fact that the ATM/PARP-2 double knockout genotype is embryonic lethal [20] further supports the involvement of PARP-2 in double strand break repair during replication.…”
Section: Parp-2 In the Maintenance Of Genomic Integritymentioning
confidence: 99%
“…The main role proposed for PARylation in genome stability is linked to the recruitment of specific proteins through PAR binding domains such as the macro domain. At replication forks, the establishment of a PAR scaffold is necessary for the reversal of forks generated by TopI inhibition [73,74]. In addition, PAR protects reversed forks from MRE11 mediated degradation by either physically impeding the access to the fork or by cooperating in the recruitment of BRCA2 and RAD51.…”
Section: Rs As a Fuel Of Tumorogenesismentioning
confidence: 99%